Balik Nama Sertipikat Hak Milik (SHM) Berdasarkan Pengikatan Jual Beli Yang Penjualnya Meninggal Dunia Di Sumatera Barat - Fatrianita Tambunan; Kurnia Warman; Syofiarti Syofiarti (Nagari Law Review, 2018)
The basic concept of land buying and selling is clearance and cash. If this concept cannot be fulfilled, it does not mean that the transactions cannot be carried out. In this situation, notary may use another instrument that is by making Commitment of Sale and Purchase Agreement (PJB). The Commitment can be made through the Commitment of PJB which is not fully paid and the agreement of the Commitment of PJB full payment. In the case the seller with the authority to sell, passed away before the signing of Commitment, the problems will arise. The first how is the process of completion of The Commitment of PJB? The second, how is the law protection on the buyer in the process of title transfer of the certificate of ownership based on The Commitment of PJB.? The third how is the title transfer of the certificate of property rights based on The Commitment of PJB? The results showed that the process of completion of the sale and purchase of land through The Commitment of PJB in which the seller passed away is carried out by tracking down the heirs, the protection of law against buyers in the process of title transfer of property certificates is done by filing a court suit to obtain a court decision. The process of title transfer of the property certificate in The Commitment of PJB agreement in can be executed by tracking down the heirs and / or by court decision